2cos^2x-3cosx+1=0 sin3x+\sqrt3 cos3x=0 2tgx-ctgx+1=0 6cos^2x+7sinx-8=0 sinxcosx-cos^2x=0...

0 голосов
148 просмотров

2cos^2x-3cosx+1=0 sin3x+\sqrt3 cos3x=0 2tgx-ctgx+1=0 6cos^2x+7sinx-8=0 sinxcosx-cos^2x=0 3tg^22x-2ctg(П/2+2x)-1=0


Алгебра (18 баллов) | 148 просмотров
Дан 1 ответ
0 голосов

2cos^2x-3cosx+1=0   замена переменной  cosx =t ;     -1=<   t =<1</span>

2t^2 - 3t +1 =0  квадратное уравнение

D =1

t1 =1/2 ; cosx =t1 =1/2 =cos(2pi*n-pi/3)=cos(2pi*n+pi/3) , n ϵ Z 

t2=1  ;cosx =t2 =1 =cos(2pi*n) , n ϵ Z 

ОТВЕТ  

x =(2pi*n) , n ϵ Z 

x=(2pi*n-pi/3), n ϵ Z 

x=(2pi*n+pi/3), n ϵ Z